Bladder filling test, cystoscopy, or both for checking bladder perforation in tension-free-vaginal tape operations: Is cystoscopy necessary in all TVT operations? - Kalkan, Uzeyir; Eren, Murat Tuğrul (Journal of Surgery and Medicine, 2022)
Background/Aim: Tension-free-vaginal tape (TVT) has been widely used for treatment of stress urinary incontinence as a mid-urethral sling operation. Cystoscopy is routinely performed during tension-free-vaginal tape operations to check for bladder perforation or injury. This study aims to check the applicability and accuracy of the bladder filling test for predicting bladder perforation in tension-free-vaginal tape operations. Methods: Between 2015 and 2020, 285 women who had TVT operations were subject to evaluation. Out of 285 cases, 23 cases were suspected subjectively by the operating surgeons to have visible or occult bladder perforation during the TVT procedure. A routine cystoscopy was performed at the end of all operations. Additionally, before the routine cystoscopy, in cases suspected of a visible or occult bladder perforation, the bladder was filled with 500 ml saline or diluted methylene blue dye through a urinary catheter (bladder filling test) to check for occult bladder perforation that might not be visualized by cystoscopy. Any fluid leakage through the paraurethral dissected canals or from the abdominal incisions was observed for the possibility of bladder perforation. The accuracy of the bladder filling test was compared to cystoscopy to diagnose bladder perforation in suspected cases. In addition, all cases were followed up for three months to record any cases with late or occult bladder perforations missed in the diagnosis using cystoscopy or the bladder filling test perioperatively. Results: Out of 23 cases suspected subjectively by the operating surgeons to have visible or occult bladder perforation, 11 had visible bladder perforations (3.9%) confirmed by both cystoscopy and the bladder filling test. After the filling test, leakage at the abdominal incision site and/or para-urethral dissected canal was observed in all cases with bladder perforation. No leakage was observed in the remaining patients (n = 12) suspected of, but not diagnosed with bladder perforation by cystoscopy. The bladder filling test did confirm the same diagnosis revealed by cystoscopy in all suspected cases. Conclusion: The bladder filling test was found to be very sensitive in predicting bladder perforation at tension-free-vaginal tape operations compared to cystoscopy. This test can decrease the need for routine cystoscopy at tension-free-vaginal tape insertion, and cystoscopy can be limited to cases with leakage in the bladder filling test.